Pengaruh Persepsi Harga, Kualitas Produk dan Tingkat Kepercayaan terhadap Keputusan Pembelian Konsumen PT. Citra Tunas Medika di Surabaya - Ika Noerma Ramadhani; Gustaf Naufan Febrianto (JURNAL RISET MANAJEMEN (JURMA), 2024)
This study aims to prove and analyze 1). The Influence of Price Perception, on Consumer Purchasing Decisions of PT. Citra Tunas Medika, 2). The Influence of Product Quality on Consumer Purchasing Decisions of PT. Citra Tunas Medika, 3). The Influence of Trust Level on Consumer Purchasing Decisions of PT. Citra Tunas Medika, 4). The Influence of Price Perception, Product Quality and Trust Level on Consumer Purchasing Decisions of PT. Citra Tunas Medika The type of data used in this study is quantitative data. The sampling technique used in this study is purposive sampling with 100 customer respondents of PT. Citra Tunas Medika. Data analysis used is multiple linear regression analysis, R2 determination, t-test and f-test. Then the data from the respondents are processed using SPSS 27, to determine the results of the Influence of Price Perception, Product Quality and Trust Level on Consumer Purchasing Decisions of PT. Citra Tunas Medika in Surabaya. The results of this study indicate that the significance value is less than 0.05 and the value of t count is greater than the table. The significance value of Price Perception (X1) is (2.256>1.984), Product Quality (X2) is (2.492>1.984), Trust Level (X3) is (2.165>1.984). Based on the formulation of the problem, the following are the results of the study and it can be concluded that Price Perception has a positive and significant effect on purchasing decisions, Product Quality has a positive and significant effect on Purchasing Decisions, Trust Level has a positive and significant effect on Purchasing Decisions.